Creating temporal abstractions in three clinical information systems. - Kahn, M. G. (American Medical Informatics Association, 1995)
Modern clinical information system developers recognize the need to associate temporal information with clinical data. However, specific clinical systems capture different temporal features using a variety of data modeling techniques. Two commonly used methods to represent temporal information are point-based events and interval-based durations. We recently implemented a rule-based expert system for drug dose monitoring on three clinical information systems. The expert system requires both static drug dosing information (drug name, amount, route, frequency) and temporal dosing information (duration of therapy, renewals, restarts). Our design goal was to use the same expert system code on all three information systems by defining a common database schema to hide differences in the original systems' data models. Although we have been successful in mapping clinical data from these three source systems into a unified temporal data representation, we describe how differences in handling time within the three clinical systems made this goal difficult to achieve.